2015
DOI: 10.25110/arqvet.v18i1.2015.5368
|View full text |Cite
|
Sign up to set email alerts
|

Sazonalidade Na Congelabilidade De Sêmen Bovino

Abstract: Eliane Vianna da Costa-e-Silva 1 QUEIROZ, V. L. D.; COSTA FILHO, L. C. C. da; ROSA, L. da S.; ZÚCCARI, C. E. S. N.; COSTA e SILVA, E. V. Sazonalidade na congelabilidade de sêmen bovino. Arq. Ciênc. Vet. Zool. UNIPAR, Umuarama, v.18, n.1, p. 39-47, jan./mar. 2015. RESUMO:O objetivo desta revisão foi apresentar e discutir os efeitos da sazonalidade nas características seminais de touros Bos taurus e Bos indicus antes e após o congelação, a fim de possibilitar maior rentabilidade econômica. Apesar da reprodução d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…During the evolution of the bovine species, zebu animals developed better tolerance to tropical climates (Hansen, 2004;Queiroz et al, 2015 The ejaculate volume did not differ during the monitored months, nor did it present differences between the subspecies. Similarly, influences of temperature and seasons were not identified in the seminal volume from crossbred Jersey bulls, however, it was identified that the management of the animals and the intervals between semen collections generated differences in the ejaculate volume (Gopinathan, Sivaselvam, Kanniappan Karthickeyan, & Venkataramanan, 2018), factors that were minimized in the present study, since all the animals had the same management and the same semen collection routine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the evolution of the bovine species, zebu animals developed better tolerance to tropical climates (Hansen, 2004;Queiroz et al, 2015 The ejaculate volume did not differ during the monitored months, nor did it present differences between the subspecies. Similarly, influences of temperature and seasons were not identified in the seminal volume from crossbred Jersey bulls, however, it was identified that the management of the animals and the intervals between semen collections generated differences in the ejaculate volume (Gopinathan, Sivaselvam, Kanniappan Karthickeyan, & Venkataramanan, 2018), factors that were minimized in the present study, since all the animals had the same management and the same semen collection routine.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is essential to select breeding bulls capable of producing spermatozoa resistant to cryopreservation and maintaining high sperm viability and fertilizing capacity after thawing. However, not all bulls are considered suitable for frozen semen production, since there are innumerable intrinsic (age, bull's health, libido) and extrinsic variables (season, feeding, management) involved in this process (Queiroz, Filho, Rosa, Zúccari, & Costa e Silva, 2015;Ram et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain good results in the use of artificial insemination, rigorous quality processes are necessary, from the management of breeding bulls to the stages of collection and cryopreservation of the semen, taking into account that the process of the semen cryopreservation causes a drop in sperm quality (Abud et al, 2014;García-Álvarez et al, 2014). Furthermore, it is essential to select breeding bulls capable of producing cryopreservation-resistant ejaculates and maintaining high sperm viability and fertilizing capacity after thawing (Ntenka et al, 2016;Queiroz et al, 2015;Ram et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, not all bulls are able to produce frozen semen, since numerous intrinsic variables (age, bull's health, libido) and extrinsic (season, diet, management) are involved in this process. (El-Harairy et al, 2011;Queiroz et al, 2015). Another important factor to be considered is the difference in semen quality between the bovine breeds and the respective aptitudes of the animals, which even lacking scientific studies, it is speculated that dairy bulls produce ejaculates with higher quality compared to beef bulls (Morrell et al, 2018).…”
Section: Introductionmentioning
confidence: 99%